Breast cancer osteomimicry and its role in bone specific metastasis; an integrative, systematic review of preclinical evidence. (December 2016) - Awolaran, Olugbenga; Brooks, Susan A.; Lavender, Verna
Abstract: Metastasis accounts for most of the deaths from breast cancer and the preference of invasive breast cancer metastasising to bone has been widely reported. However, the biological basis of breast cancer osteotropism is not fully understood. This paper provides, for the first time, an integrative, systematic review of evidence of molecular factors that have functional roles in the homing of metastatic breast cancer to the bone. Pubmed, Web of Science and EBSCOhost were searched using keywords and synonyms for molecular, metastasis, breast cancer and bone to identify articles published between January 2004 and August 2016. 4491 potentially relevant citations were retrieved. 63 articles met the inclusion criteria, which were primary studies reporting evidence of molecular factors that have functional roles in predisposing breast cancer bone metastasis in vivo . 12 of those 63 articles that additionally met quality criteria were included in the review. Extracted data were tabulated and key findings that indicated biological mechanisms involved in breast cancer metastasis to bone were synthesised. 15 proteins expressed by breast cancer cells were identified as factors that mediate breast cancer bone metastasis: ICAM-1, cadherin-11, osteoactivin, bone sialoprotein, CCN3, IL-11, CCL2, CITED2, CXCR4, CTGF, OPN, CX3 CR1, TWIST1, adrenomedullin and Enpp1. Upregulation or overexpression of one or more of them by breast cancer cells resulted in increased breast cancer metastasis to bone in vivo, except for CCL2 where bone-metastatic cells showed a reduced expression of this factor. All factors identified, here expressed by breast cancer cells, are proteins that are normally expressed in the bone microenvironment and linked to physiologic bone functions. All have a functional role in one of more of the following: cell proliferation and differentiation, bone mineralization and remodelling, cell adhesion and/or chemokine signalling. Six of them (cadherin-11, ICAM-1, OPN, CX3 CR1, CCN3 and osteoactivin) have a reported function in cell adhesion and another eight (CCN3, osteoactivin, Enpp1, IL-11, CTGF, TWIST1, adrenomedullin and CITED2) are reported to be involved in cell proliferation and differentiation. This review collates and synthesises published evidence to increase our understanding of the biology of breast cancer osteomimicry in the development of bone metastasis. Findings of this review suggest that changes in expression of proteins in breast cancer cells that confer osteomimicry facilitate homing to bone to enable the development of bone metastasis. Highlights: 15 proteins were identified as factors that promote breast cancer bone metastasis. Expression of these factors by breast cancer cells mediate osteotropic metastasis. All factors identified are proteins that are normally expressed in the bone microenvironment. Breast cancer cell protein expression conferring osteomimicry facilitates osteotropic metastasis.